Healthy Living Culture Learning Media Based on the "E-BHS" Application for Elementary Schools - Trinando, Jeffry; Muhammad Suhron Siregar; Walam Yudiani; Palmizal A; Wawan Junresti Daya (Indonesian Journal of Sport and Tourism, 2025)
Healthy living culture education is a fundamental aspect in the formation of elementary school students' character. This study developed an interactive learning media based on a mobile application called "E-BHS" (Electronic-Healthy Living Culture), which is specifically designed for elementary school students. This application integrates healthy living culture learning materials with digital technology that is interesting and easy for children to understand. Through a quantitative approach with an experimental design, this study involved 60 students in grades IV-VI from three elementary schools. The results showed that the use of the E-BHS application could increase students' understanding of healthy living culture by 78% compared to conventional learning methods. This application has been proven effective in increasing learning motivation, student involvement, and the application of healthy living practices in everyday life.